Effect of Incubation of Coconut Coir Biochar and Liquid Organic Fertilizer on Nutrient Uptake of Mustard Samhong King (Brassica rapa subsp. chinensis) - Putri Nadia Riana; Zaitun Zaitun; Syakur Syakur (Jurnal Ilmu Pertanian Indonesia, 2025)
Green mustard greens. Samhong King variety (Brassica rapa subsp. chinensis) is a popular vegetable in Indonesia. Green mustard greens have the advantage of being able to grow in both low and high elevations. The application of biochar in soil can help to improve its chemical qualities. The study employed a factorial randomized block design with two components. The treatment factor was the incubation duration of coconut fiber biochar at four levels: control, two weeks, four weeks, and six weeks. The amount of liquid organic fertilizer applied at four different levels: 1 mL/L water, 2 mL/L water, 3 mL/L water, and 4 mL/L water.The study found that coconut fiber biochar and liquid organic fertilizer had no significant effect on nutritional absorption in plant tissue or Samhong King mustard plants, however they did have the highest absorption of K, P, and N nutrients. The incubation period of coconut fiber biochar and liquid organic fertilizer had no significant effect on Samhong King mustard plant production, but the coconut fiber biochar treatment with a 6-week incubation period produced the highest yield, 2.96 t/ha. The treatment of liquid organic fertilizer yielded the best results. Keywords: Brassica rapa subsp. Chinensis, mustard Samhong King, plant nutrients, soil improver